2005
DOI: 10.1038/sj.leu.2403719
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunomodulatory treatment based on conventional and lineage-specific chimerism analysis in patients with myeloid malignancies after myeloablative allogeneic hematopoietic cell transplantation

Abstract: Both conventional chimerism analysis (CCA) and lineagespecific chimerism analysis (LCA) have potential pitfalls as diagnostic means for the detection of minimal residual disease after allogeneic hematopoietic cell transplantation (aHCT). Therefore, the present study examines the results of both methods in order to determine how predictive consecutive evaluations were, with respect to the risk that the patient would relapse during post-transplant follow-up and with respect to responsiveness to immunomodulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 34 publications
2
46
2
Order By: Relevance
“…[13][14][15] AML patients commonly express CD34 Ag (70-75%) on their malignant cells and in some cases the leukemic immunophenotype can alter from diagnosis to relapse. 18,19 Our analysis included patients with CD34 Ag expressing AMLs and 23 patients with, at first diagnosis CD34 À AML (all of these patients were in the control group with stable DCC), which might be a limitation of lineage-specific DCC analysis in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] AML patients commonly express CD34 Ag (70-75%) on their malignant cells and in some cases the leukemic immunophenotype can alter from diagnosis to relapse. 18,19 Our analysis included patients with CD34 Ag expressing AMLs and 23 patients with, at first diagnosis CD34 À AML (all of these patients were in the control group with stable DCC), which might be a limitation of lineage-specific DCC analysis in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lineage-specific donor chimerism analysis of flow cytometry-sorted CD34 þ cells are highly specific for monitoring MRD in diseases with CD34 expression on malignant cells. [13][14][15][16] fludarabine, or either treosulfan or BU i.v in combination with fludarabine. Standard-intensity conditioning, mainly consisting of fractionated 12 Gy TBI and CY was employed in 16% (n ¼ 22).…”
Section: Introductionmentioning
confidence: 99%
“…86 This encouraging experience is contrasted by observations of more limited and largely temporary effects of such pre-emptive measures in acute leukemia, suggesting insufficiency to prevent overt relapse in many patients. 35,39,[87][88][89][90] Additional (pre-emptive) post-HCT therapy Useful additional post-HCT therapy could encompass conventional chemotherapies (ideally non-cross-resistant to those used for prior therapies), Ab-based therapeutics, epigenetic modifying drugs and/or molecularly targeted agents. Supporting this strategy, Platzbecker et al 91 observed that 16 out of 20 patients with CD34 þ AML or myelodysplastic syndromes who received the DNA methyltransferase I inhibitor, azacitidine, after they experienced a decrease in CD34 þ donor chimerisms to o80% responded with either increasing donor chimerism or stabilization thereof.…”
Section: Using Pre-hct Mrd To Tailor Therapy In Acute Leukemiamentioning
confidence: 99%
“…33 A prognostic value has been attributed to quantitative lymphocyte and neutrophil recovery, especially for myeloid neoplasia after allogeneic SCT. [34][35][36] Attempts are made to diagnose 2,3 and treat 11,12 incipient relapse based on parameters such as NPM1 mutations, 7,9,10,37,38 WT1 overexpression [37][38][39][40] and donor-patient chimaerism [41][42][43] or combinations of those. 13 Yet, apart from chimaerism, those methods are frequently available for a limited set of patients (for example, NPM1 mutations).…”
Section: Discussionmentioning
confidence: 99%